The determinants of credit spreads changes in global shipping bonds - Kavussanos, Manolis G.; Tsouknidis, Dimitris (My University, 2014)
This paper investigates whether bond, issuer, industry and macro-specific variables account for the observed variation of credit spreads' changes of global shipping bond issues before and after the onset of the subprime financial crisis. Results show that conclusions as to the significant variables of spreads depend significantly on whether two-way cluster-adjusted standard errors are utilized, thus rendering results in the extant literature ambigious. The main determinants of global cargo-carrying companies' shipping bond spreads are found in this paper to be: the liquidity of the bond issue, the stock market's volatility, the bond market's cyclicality, freight earnings and the credit rating of the bond issue.
Keywords: Bond spreads; Panel data; Shipping; Shipping finance; Two-way clustered standard errors